2004
DOI: 10.1103/physrevb.69.054401
|View full text |Cite
|
Sign up to set email alerts
|

Competing electronic ground states inLa1xCaxCoO

Abstract: We present the results of a neutron powder-diffraction study on La 1Ϫx Ca x CoO 3 . We show that, contrary to previous reports, a first-order structural transition R3 c→ Pnma occurs as a function of both x and T. Spin-state transitions occur as a function of x, T as indicated by the changes in cell volume, with evidence of a macroscopically inhomogeneous spin-state mixture at xϭ0.1. The magnetic behavior generally parallels that of La 1Ϫx Sr x CoO 3 , with evidence for both spin-glass behavior and ferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…It is now established that La 0.5 Sr 0.5 CoO 3 exhibits a glassy magnetic behaviour (Wu et al 2005). Recent studies of the magnetic and electrical properties of several members of the Ln 1Kx A x CoO 3 family have revealed that they are electronically phase-separated (Burley et al 2004;Kundu et al 2005a;Wu et al 2005). The phase separation is favoured by small hr A i as well as size disorder (Kundu et al 2006).…”
Section: Electronic Phase Separation In Rare-earth Cobaltatesmentioning
confidence: 99%
“…It is now established that La 0.5 Sr 0.5 CoO 3 exhibits a glassy magnetic behaviour (Wu et al 2005). Recent studies of the magnetic and electrical properties of several members of the Ln 1Kx A x CoO 3 family have revealed that they are electronically phase-separated (Burley et al 2004;Kundu et al 2005a;Wu et al 2005). The phase separation is favoured by small hr A i as well as size disorder (Kundu et al 2006).…”
Section: Electronic Phase Separation In Rare-earth Cobaltatesmentioning
confidence: 99%
“…Moreover, Nagaev et al [11] have predicted that magnetic exciton formation is the precursor for magneto-electronic phase separation at high hole (electron) densities. Such a phase separation has been observed in LaCoO 3 doped with divalent cations such as Sr [12,13] and Ca [14]. The nature of a magnetic polaron or exciton implies that it may be most easily observed in a system displaying a diamagnetic ground state, making LaCoO 3 an ideal candidate to study such an defect-driven magnetic state.…”
mentioning
confidence: 99%
“…The competition between different spin states has caused large controversy in the literature previously [10,[12][13][14][15][16][17][18][19], but in most studies only the case of LaCoO3 has been considered. Different studies favor either a LS to IS or a LS to HS state transition by heating across Ts1 ≈ 75 K [20][21][22][23][24]. Furthermore, a low temperature magnetic defect structure has been commonly observed in LaCoO3, which can be explained by the existence of magnetic polarons or excitons [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%